2007
DOI: 10.1097/ajp.0b013e3181565cf1
|View full text |Cite
|
Sign up to set email alerts
|

Physician Attitudes Toward Opioid Prescribing for Patients With Persistent Noncancer Pain

Abstract: Factors shown to have an adverse affect on opioid prescribing disproportionately impact on the attitudes of internists compared with geriatricians. Further research is needed to determine if there is also a differential impact on how internists care for their elderly patients with chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 17 publications
1
47
0
Order By: Relevance
“…cal dependence, tolerance and addiction [21][22][23][24][25] ; concern about possible diversion of opioid medication for other purposes 12,15,23,24,[26][27][28][29] ; and concern about possible sanctions by state and federal regulatory agencies. 21,27,28,[30][31][32][33] These concerns may complicate clinical decision making regarding the prescription of opioids 34,35 and may result in extra time demands, failures in the patient-physician relationship, and less time on other activities.…”
Section: O Pioid T Her a P Y A Nd Pr E V En T Iv E Serv Ic Esmentioning
confidence: 99%
“…cal dependence, tolerance and addiction [21][22][23][24][25] ; concern about possible diversion of opioid medication for other purposes 12,15,23,24,[26][27][28][29] ; and concern about possible sanctions by state and federal regulatory agencies. 21,27,28,[30][31][32][33] These concerns may complicate clinical decision making regarding the prescription of opioids 34,35 and may result in extra time demands, failures in the patient-physician relationship, and less time on other activities.…”
Section: O Pioid T Her a P Y A Nd Pr E V En T Iv E Serv Ic Esmentioning
confidence: 99%
“…The attitude of the physician affects the prescription of opioids for patients with CNCP. In a survey by Lin et al [12], most physicians strongly agreed that they were hesitant to prescribe opioid analgesics because of concerns about side effects (58%), diversion for illegal use (37%), and causing addiction (31%). In fact, a recent meta-analysis [4] revealed that many patients withdrew from clinical trials due to adverse effects (oral, 32.5%; intrathecal, 6.3%; transdermal, 17.5%).…”
Section: Discussionmentioning
confidence: 98%
“…A number of potentially serious adverse effects and aberrant behaviors such as opioid abuse, addiction, and diversion make it difficult for physicians to prescribe opioids liberally 56 . Therefore, not only the under-treatment of pain is recognized as a major problem for patients which has societal implications 6 but also the opioids are underutilized drugs for chronic pain especially in elderly 57 due to physician’s concerns about the uncertain efficacy, untoward side effects and addiction 58, 59 .…”
Section: Discussionmentioning
confidence: 99%